Republic of Kazakhstan : Financial System Stability Assessment-Update including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision and Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents an update on Kazakhstan's Financial System Stability Assessment including Reports on the Observance of Standards and Codes on Banking Supervision and Anti-Money Laundering and Combating the Financing of Terrorism. Kazakhstan has made impressive improvements in its financial sector legislation, and has revamped its institutional structure for financial sector oversight. The financial sector, which is dominated by banks, has been one of the fastest-growing sectors of the economy. This has been facilitated by a favorable macroeconomic environment helped by a cautious fiscal stance and increasing oil revenue.